Performance of rubber seed oil as an alternative to diesel in oil-based drilling mud formulation - Amanze Josiah Destiny; Fortune Chukwuebuka Amanze (Institute of Advanced Engineering and Science, 2021)
The formulation of an oil-based mud was made possible with the oil extracted from rubber seeds using the famous Soxhlet extraction method. The mud was formulated using the American Petroleum Institute (API) standard of 25 g of bentonite to 350 mL base fluid. The choice of rubber oil comes as a result of its flash point and aniline point which lie in the range of base oils used for mud formulation. The rheological properties of the rubber oil-based mud (OBM) were beyond the scope of the viscometer and hence thinner was added to reduce its viscosity and its suitability to compete favorably with diesel OBM was checked. The 10 sec and 10 min gel strength of the rubber OBM were recorded as 68 lb/100 ft2 and 69 lb/100 ft2 respectively while that of Diesel was 65 lb/100 ft2 and 67 lb/100 ft2. The plastic viscosity of rubber OBM was 12 cp while that of Diesel was 17 cp. They both exhibited Bingham Plastic behavior and a similar yield point of 146 lb/100 ft2. The formulated mud samples were subjected to temperatures of 60 ºC and 75 ºC and it was discovered that rubber OBM was more likely to retain its rheological property than diesel OBM. Comparison with other rheological properties of diesel OBM showed that the formulated mud could be used alternatively for diesel in drilling operations.